Feeding evolution of a herbivore influences an arthropod community through plants: implications for plant‐mediated eco‐evolutionary feedback loop. (July 2015) - Utsumi, Shunsuke; Shefferson, Richard
Summary Genetic variation in individual species can have important ecological consequences, and sometimes, these interactions are mediated through another species. For example, genetic variation in an herbivore could alter plant responses that then influence other plant‐associated arthropods. However, few systems have experimentally tested the ecological consequences of genetic variation as mediated through other species, especially within the same trophic community context. I studied how evolution of feeding preference in the willow leaf beetle (Plagiodera versicolora), which occurs under selection in a herbivore community context, feeds back to an arthropod community through plant‐mediated indirect interactions. Previous studies show beetle populations locally adapt distinct preferences ranging from the gourmet‐type, which feeds exclusively on new leaves of willows, to the no‐preference (no‐pref) type, which displays non‐preferential feeding on leaves of different ages. I conducted field experiments at two sites that mimicked evolutionary changes in the feeding preference of the leaf beetle. I manipulated the composition of leaf beetle feeding types for 6 days in spring and then investigated subsequent development of arthropod communities. I found that initial herbivory by a higher proportion of gourmet‐type beetles led to lower subsequent abundance of conspecific beetle larvae. In contrast, a higher proportion of gourmet‐type beetles resulted in higher abundance of aphids. Aphid‐tending ants also increased with the increasing abundance of aphids. As a result, species diversity of arthropod communities decreased with the proportion of gourmet‐type beetles in the initial beetle treatment. Community assembly dynamics were significantly influenced by interactive effects between the initial beetle treatment and subsequent colonizer species identities. Thus, beetle genetic variation had long‐lasting effects through a temporal chain of indirect interactions likely mediated through induced plant responses and the abundance of aphids. Synthesis. Evolutionary changes in feeding traits within an herbivore species had profound but predictable impact on local arthropod communities. Because the feeding evolution of herbivores nearly always occurs in a community context, plant‐mediated feedback loops between the evolution and ecological community of arthropods may be widespread in nature.